Pengaruh Upah, Kesempatan Kerja dan Indeks Pembangunan Manusia terhadap Pengangguran Terdidik di Sumatera Barat - Nabila Ayu Prasetya; Idris (Universitas Negeri Padang, 2025)
This research aims to analyse the influence of wages, job opportunities and human development index (IPM) on educated unemployment in West Sumatra during the 2019–2023 period in 19 districts and cities. The approach used is quantitative with the panel data regression method. The data used is secondary data from the Central Statistics Agency (BPS) of districts/cities in West Sumatra Province. The analysis tool used is panel data regression analysis with the Eviews 13 program. The results of the analysis show that wages have a negative and significant effect on educated unemployment in West Sumatra, job opportunities have a negative and significant effect on educated unemployment in West Sumatra, while IPM has a positive and significant effect on educated unemployment in West Sumatra. Wage variables, job opportunities and human development index (IPM) together have a significant effect on educated unemployment in West Sumatra.